Resource use efficiency and yield determinants in rapeseed-mustard cultivation: an integrated approach using Cobb-Douglas, Monte Carlo, and sensitivity analysis - Rathour, Sachin; Kumari, Meera; Singh Badal, Prakash; Kamalvanshi, Virendra; Kushwaha, Saket; Jatav, Hanuman Singh; Devegowda, S. R. (Frontiers in Agronomy, 2025)
Rapeseed-mustard (Brassica spp.) is one of the most significant oilseed crops globally, with India being a major contributor, accounting for 11% of world production. Despite advancements in mustard cultivation practices, there remains a lack of comprehensive analysis integrating resource efficiency and input interactions to optimize yields sustainably. Furthermore, limited studies have employed advanced methodologies to assess the impacts of input uncertainties on yield stability and risk management. Therefore, the study evaluated the resource use efficiency in mustard cultivation through the Cobb-Douglas production function, Monte Carlo simulations, offering insights into input utilization and yield variability under uncertain conditions and sensitivity analysis for specific inputs’ contribution to yield. Results revealed imbalances in resource utilization; land and soil qualities are underutilized, while labor, plant protection chemicals, and machinery are overutilized. Fertilizer and seed inputs emerged as significant positive influencers of yield, with sulphur and fertilizer identified as critical factors through sensitivity analysis. Monte Carlo demonstrates yield stability, predicting a 100% probability of achieving at least 6 quintals per acre (1483 Kg/ha) under current input conditions. Policymakers can design targeted interventions to reduce regional productivity disparities and foster sustainable growth in the rapeseed-mustard sector. Findings also underscore the need for optimizing input utilization to balance economic, agronomic, and environmental outcomes, as well as adopting better practices for India’s oilseed sector.